2020
DOI: 10.1111/gcbb.12742
|View full text |Cite
|
Sign up to set email alerts
|

Corn stover harvest reduces soil CO2 fluxes but increases overall C losses

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Another recent Iowa study, with similar climate (same average mean annual temperature and precipitation) and soil (Mollisol) conditions, showed that grain yield response to maize stover removal was dependent on tillage system (O'Brien et al., 2020). Similar to our study, they found that for conventional tillage systems, stover removal increased yield compared to a no removal treatment from 2010 to 2012, while for no‐till systems, removing maize stover increased yields only in the wettest year (O'Brien et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent Iowa study, with similar climate (same average mean annual temperature and precipitation) and soil (Mollisol) conditions, showed that grain yield response to maize stover removal was dependent on tillage system (O'Brien et al., 2020). Similar to our study, they found that for conventional tillage systems, stover removal increased yield compared to a no removal treatment from 2010 to 2012, while for no‐till systems, removing maize stover increased yields only in the wettest year (O'Brien et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Another recent Iowa study, with similar climate (same average mean annual temperature and precipitation) and soil (Mollisol) conditions, showed that grain yield response to maize stover removal was dependent on tillage system (O'Brien et al., 2020). Similar to our study, they found that for conventional tillage systems, stover removal increased yield compared to a no removal treatment from 2010 to 2012, while for no‐till systems, removing maize stover increased yields only in the wettest year (O'Brien et al., 2020). Overall, those results suggest moderate stover harvest will likely have a neutral or even positive effect for this midwestern U.S. area, and is consistent with several prior studies conducted under similar climate soil conditions (Birrell et al., 2014; Karlen et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…A long‐term experiment was conducted from 2008 to 2021 at the Iowa State University Agricultural Engineering and Agronomy Research Farm (42.017584°, −93.76448°) to assess the effects of corn stover removal on soil health, SOC content, and crop yields (O'Brien et al., 2020; Obrycki et al., 2018). The site is located within a Webster–Clarion soil complex, with poorly‐drained Webster soils on 0%–2% slopes and moderately well‐drained Clarion soils on 2%–5% slopes.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental plots (85.3 m × 12.2 m each) with continuous corn production had three levels of corn stover removal: none, a moderate level, and a high level, equating to approximately 0%, 35%, and 60% of the stover biomass and to 0%, 50%, and 100% of what was mechanically feasible to harvest (O'Brien et al., 2020; Obrycki et al., 2018). Actual stover yields averaged over 2008–2020 were 3.5 ± 1.1 and 5.0 ± 1.7 Mg ha −1 for the moderate and high removal levels, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Soil hydrolases such as β-1,4-glucosidase (BG) and cellobiohydrolase (CBH) mainly acquire labile carbon [20]. Research shows that the combined application of different crop straw or biochar can improve the activity of soil carbon-degrading enzymes and increase soil organic carbon content [21,22] while increasing soil carbon emissions [23,24]. Therefore, clarifying the dynamic changes of soil enzymes is key to understanding the changes in the carbon pool caused by different straws being returned to the field.…”
Section: Introductionmentioning
confidence: 99%